Distribuição e correlação dos parâmetros físicos e químicos do solo em área úmida do cerrado aplicando modelos matemáticos - Almeida, Fabrício Pelizer de (2016)
Wetlands in tropical regions constitute an important frontier of knowledge due to the complexity of the mineralogical constituents of the biogeochemistry dynamic and the roles it plays in maintaining the Cerrado biome sustainability. Occur in these areas of topographic depression, hydromorphic soils, characterized by the condition of poor drainage and waterlogging. Already in Plains occur when replaying morphological patterns, characterized as lots of semielliptical lands and depressions, known as \'murundus fields . Two thoughts talk about their training, one that deals with the geomorphological origins of large heaps, describing them because of differential erosion of the land, and another that assigns to the biological origin, which would be promoted by mesofauna, primarily by termites, so cumulative usually. In the microregion of Uberlândia in the Triângulo Mineiro (MG) presents several murundus fields, in the transition between the plateau (drained) and areas of depression. The objectives of this research were to determine the biogeochemical aspects of morphological and murundus, from chemical, physical and biological indicators, and assessing the ability of mathematical models about the interactions and correspondence of variables and the optimization and simulation of indicators in a same catena. The data obtained from soil analysis reports sampled, correspond to open trenches in areas of murundus, plateaus, edge and center of the depression, surface and depth, and understand the complex sorptive, total oxides and textural aspects. The highest coefficients of significant response to organic matter in generalized linear model (GLM), were obtained in the areas of border and Central depression (10.14 and 11.84, respectively), but decrease quickly, varying greatly from one stratum to another deep (-7.45 and 5.01 of 51-100 cm, respectively). Although smaller significant coefficients observed in the GLM, to murundus areas in (8.13 of 00-20 cm; 5.57 of 21-50 cm), more uniform trend was observed as to the variation up to 100 cm (3.04 of 51-100 cm). The traces of the hydromorphy and bioturbation activity in the fields of large heaps are indispensable for understanding the dynamic character of heterogeneization of profile and primarily, of accumulation of organic matter and increase cargo complex on the ground. On the plateau, in all the proposed mathematical models, it has not been possible to observe significant response capacity to the levels of organic matter. Multivariate non-hierarchical models, contacted if more correspondence between the factors that make up the complex indicators sorption (grouped) and the areas represented by the environments with any trace of hydromorphy (mu, T1P2) or typically hydromorphic (bd, T1P3; cd, T1P4), reiterating the composition of the generalized linear model. As for the overlay simulation of responses, it was evidenced only strong resemblance between the murundus and the edges of the depression, as the behavior of the relationship Fe(OH)3/Al2O3. The results of simulation and optimization demonstrated that the murundus areas with better set of geomorphological attributes for MO content expression and values of CTC, under a minimum parameter range of Al2O3 (34.9487%) and a maximum range of Fe(OH)3 (9.2278%).